RARE PRESENTATIONOF A FRONTOORBITAL MUCOCELE : CASE REPORT - RAKOTONDRAIBE, Willy Francis; Patrick Maholisoa RANDRIANANDRAINA,; Tony Radotina ANDRIANAIVO,; Joseph Synèse BEMORA,; Willy RATOVONDRAINY,; Mamiarisoa RABARIJAONA,; Clément ANDRIAMAMONJY, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Mucoceles are cystic lesions from mucous tissue of para nasal sinuses. Their evolution is usually long and silent until opthalmological and or rhinological complications appeared. The authors reported a case with giant frontoethmoidal mucocele resulting in headache and unilateral visual loss. CT scan revealed cystic extension into the anterior cranial fossa with erosion of both posterior tables of frontal bone. The cyst was expanding into the orbit causing bone destruction of the medial wall of the orbit. The lesion was cured by a transcranial approach. Pathogenesis, surgical procedure and prognosis are discussed.